Ціннісне ставлення до довкілля як чинник розвитку особистості в юнацькому віці - Кордунова, Наталія Олександрівна; Потапчук, Людмила Володимирівна; Kordunova, Nataliia O.; Potapchuk, Liudmyla V. (Інститут психології імені Г. С. Костюка НАПН України, 2014)
Стаття присвячена дослідженню актуальної проблеми ціннісного ставлення до довкілля особистості. Розглядаються різнобічні підходи у дослідженні проблеми вивчення ціннісного ставлення до довкілля як важливого чинника розвитку особистості в юнацькому віці. Автори аналізують різні аспекти цього особистісного процесу. Особливу увагу приділено вивченню екологічних цінностей особистості, які визначають пріоритетну сферу в процесі взаємодії з природним середовищем в юнацькому віці. Визначено психологічні умови формування ціннісного ставлення юнаків і дівчат у процесі взаємодії з довкіллям. Акцентується увага на необхідності емпіричного дослідження зазначеної проблеми.

The article deals with the different approaches in the investigation of problems of reasonable attitude to the environment as an important factor of the personality development in adolescence. Different aspects of this personal process are analyzed. Particular attention is paid to the study of environmental value of personality that define a priority area in the process of interaction with the natural environment. Psychological conditions of boys' and girls' reasonable relationship formation in the process of interaction with the environment have been determined. The authors focus on the necessity of empirical study of this problem. A special attention is focused on the scientists'current views of understanding environmental value as an important factor of the personality development. The basic approaches to the research of this problem as a psychological phenomenon are highlighted. The comprehention role of environmental value and environmental attitudes of the personality formation of contemporary youth is singled out. Theoretical analysis of such scientific sources illustrates that the research of environmental value in psychology associated with the names of I. Bekh, O. Zdravomyslova, S. Deryabo, M. Kiselev, V. Krysachenka, V. M. Reimers, K. Rogers, V. Skrebtsya, O. Sulatskova, O. Sukhomlinska, N. Tarasenko, Y. Shvalb and others. Much attention is drawn the fact that the medium of environmental value is a man and his lifestyle where needs skills, behaviors, and the most important value system according to ecological reality is connected. Environmental value is an important part of environmental identity of adolescence formation has singled out. This period is a period of intense formation of value system and influences on the personality formation. At this age there is accumulation of sufficient moral experience, certain social status and it is actual research in environmental psychology.
Reasonable attitude to the environment as a factor of personality development in adolescence
Keywords: довкілля; юнацький вік; духовність; мораль; особистість; розвиток; свідомість; цінності; spirituality; identity; morality; natural environment; development; consciousness; formation; factor; values; adolescence